2021
DOI: 10.1111/ppc.12723
|View full text |Cite
|
Sign up to set email alerts
|

The effect of empathy skills of psychiatric nurses on their attitudes and practices towards the use of physical restraint

Abstract: Purpose The aim of this study was to evaluate the effect of empathy skills of psychiatric nurses on their attitudes and practices towards the use of physical restraint. Design and Methods This cross‐sectional, correlational, descriptive study included 100 nurses (88.49% of the population). Data were collected using a sociodemographic characteristics form, the empathy skills scale (ESS) form B, and the knowledge, attitudes, and practices of staff towards physical restraints questionnaire (KAPS‐PR) were used. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The level of empathy among caregivers is essential in reducing the use of physical restraint. [27][28][29] Studies have shown that patients experience emotional distress such as anger, helplessness, sadness, embarrassment, and punishment as a result of physical restraint. 4,5,30 Patients may also feel a loss of self-worth, degradation, and humiliation, and their autonomy and privacy may be violated when restrained.…”
Section: Discussionmentioning
confidence: 99%
“…The level of empathy among caregivers is essential in reducing the use of physical restraint. [27][28][29] Studies have shown that patients experience emotional distress such as anger, helplessness, sadness, embarrassment, and punishment as a result of physical restraint. 4,5,30 Patients may also feel a loss of self-worth, degradation, and humiliation, and their autonomy and privacy may be violated when restrained.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of adverse consequences that can be associated with using physical restraints has led institutions to introduce rigorous guidelines limiting their use to the minimum practicable extent (George, 2020). Earlier research identified empathy as a core predictor of nursing attitudes and behaviours able to prevent the occurrence of restraint use (Yıldırım Üşenmez & Gümüş, 2021). Generally speaking, empathy refers to the ability to understand others' experiences vicariously and identifies it as a crucial component of human adaptive social functioning (Davis, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The PRQ is an instrument to measure nurses' knowledge, practice, and attitudes regarding physical restraint. This instrument and its various language versions have been used in inpatient psychiatric settings in Hong Kong [30], Finland [31], India [32], Malaysia [33], Saudi Arabia [26], Sudan [11], and Turkey [34][35][36].…”
Section: Introductionmentioning
confidence: 99%